An Agent-Based Approach for Data Fusion in Homeland Security - Castillo Chamorro, José Miguel; de Solís Montes, D. Rafael (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
This article presents an agent-based solution for data fusion in Homeland Security. Communication technology has been developed very fast in the last decades. We can get lots of data in milliseconds. Our current problem is to process such amounts of data in order to provide useful information. We have to focus our effort on developing intelligent information systems able to handle big amounts of data extracting or revealing relations among data and able to produce information easily understandable for the human user. That is the case of data fusion in tactical operations, especially in the field of defense and Homeland security. Our research is focused on obtaining a Multi-agent system able to inference future enemy’s actions or behaviors from data received from heterogeneous sensors.
Keywords: MAS; data fusion; tracks; merge; inference; homeland security; IJIMAI